The Switching Lemma 205
signed by ρ.IfA ⊆ X,wewriteρ(A)=A if no variable of A is assigned
by ρ,thatis,ifρ(x)=x for all x ∈ A. For any term M,eitherρ(M)=0
or M ≤ ρ(M ).
Because ρ is a homomorphism, it preserves ≤.ThusifM ≤ ϕ, then
ρ(M) ≤ ρ(ϕ). One can show that any minterm N of ρ(ϕ)isρ(M)forsome
minterm M of ϕ (Miscellaneous Exercise 80). However, it is not true that
ρ(M) is a minterm of ρ(ϕ) whenever M is a minterm of ϕ. For example,
if ψ =(x ∨ z) ∧ (y ∨
z)andρ(x)=x, ρ(y)=y,andρ(z)=0,thenxy
is a minterm of ψ and ρ(xy)=xy, but xy is not a minterm of ρ(ψ)=x.
However, we have the following special case.
Lemma H.1 Let ϕ be a formula, C aclause,andM ∈ m(ϕ ∧ C).Letvar(M,C) be the
set of variables that occur in both M and C (not necessarily with the same
polarity ).Letσ :var(M, C) →{0, 1} be the unique valuation such that
σ(M) =0.Thenσ(ϕ ∧ C)=σ(ϕ) and σ(M) is a minterm of σ(ϕ).
Proof. The valuation σ is unique, because there is only one way to assign
values to variables in var(M,C) so that the corresponding literals in M get
the value 1. Because M must contain a literal of C,thesetvar(M,C)is
nonempty and σ(C)=1,thusσ(ϕ ∧C)=σ(ϕ) ∧ σ(C)=σ(ϕ).
The term M can be written as a conjunction of terms M = σ(M)M
,
where M
contains all the variables in var(M, C). Note that σ(M)contains
no variables in var(M,C). Similarly, ϕ can be written as a conjunction
ϕ
0
∧ϕ
1
,whereϕ
1
is a CNF formula each of whose clauses contains a literal
of M
and ϕ
0
is a CNF formula none of whose clauses contains a literal of
M
.Thenσ(ϕ) ≤ ϕ
0
and M
≤ ϕ
1
∧ C.
We now show that σ(M) is a minterm of σ(ϕ). Surely σ(M) ≤ σ(ϕ),
because M ≤ ϕ.IfN were any other term such that σ(M) ≤ N ≤ σ(ϕ),
then
M = σ(M)M
≤ NM
≤ σ(ϕ) ∧ ϕ
1
∧C ≤ ϕ ∧ C.
But M is a minterm of ϕ ∧ C, therefore M = σ(M)M
= NM
. Because
σ(M)andM
are on disjoint sets of variables, σ(M)=N. 2
Lemma H.2 Let ϕ be a formula and W a set of variables. Let
ϕ
−W
def
=
τ :W →{0,1}
τ(ϕ).
(i) If ϕ is written in CNF, then ϕ
−W
is equivalent to a CNF formula
with no more clauses than ϕ.
(ii) If M ∈ m(ϕ) such that var(M,W)=∅,thenM ∈ m(ϕ
−W
).
(iii) If ρ(W )=W ,thenρ(ϕ)
−W
= ρ(ϕ
−W
).